Pakistan Army Green Book 1994 : Training in the Army - Pakistan Army; Editorial Board : Brig. Abdul Mustaan; Lt. Col. Ghulam Jilani Khan; Lt. Col. Muhammad Marghub and Lt. Col. Muhammad Farooq Khan (GHQ, Rawalpindi Pakistan Army, 1994)
The views expressed in this book are those of the authors and not to be taken as the official opinion or policies of the General Headquarters.
Include Color Illustration
Keywords: Pakistan. Army -- Pakistan. -- Army -- Periodicals